Recurrent Spontaneous Pneumothorax in a Maltese Dog with Endogenous Lipoid Pneumonia - Alberigi, Bruno; Bendas, Alexandre; Soares, Denise do Vale; Machado, Loide; Rodrigues, Ana Carolina; Paiva, Jonimar Pereira (Acta Scientiae Veterinariae, 2021)
Background: Pneumothorax is a clinical condition which can cause respiratory distress. It can have as its origin traumatic causes or even classified as spontaneous, mainly related to diseases of the lung parenchyma. Lipoid pneumonia is rarely described in dogs, and it is characterized by globules of lipid in the alveolar spaces. Endogenous lipoid pneumonia (EnLP) occurs when lesions on pulmonary cells release cholesterol and other lipids in the alveoli. There is no clinical approach established for EnLP in veterinary patients. The aim of this report is to describe a case of a young Maltese dog, with recurrent spontaneous pneumothorax in which EnLP was diagnosed Post mortem. Case: A 2-year-old sexually intact male Maltese dog was evaluated for restrictive dyspnea. Clinicopathologic findings included cyanotic, muffled chest auscultation with hypersonic thoracic percussion. Chest x-ray demonstrated an increase in pleuropulmonary radio transparency and a floating-looking heart, indicating pneumothorax. Complete blood counts andbiochemical panel results were normal. Dirofilaria immitis antigen test results were negative. Computed tomography demonstrated slightly hyper-expanded pulmonary fields, with slightly enlarged reticular marking with areas of mild multicentric panlobular emphysema and a fracture on the sixth left rib. The treatment was focused on improving the breathing pattern through sedation, supplementation with oxygen, and thoracentesis. Owing to the reserved prognosis of the case, the unknown etiology of the recurrent pneumothorax, and the clinical worsening of the patient, the owner opted for euthanasia. Necropsy displayed multiple, circular whitish areas in the lungs, distributed over the surface of all lobes. Histopathological examination revealed pulmonary tissue with the subpleural micronodular foci, multifocal to coalescent, with a moderate accumulation of foamy intra-alveolar macrophages, occasionally multinucleate, associated with cholesterol crystals compatible with endogenous lipid pneumonia. Discussion: The patient presented with clinical signs and physical examination characteristics of pneumothorax at the first visit. After the pneumothorax diagnosis, and clinical stabilization of the patient. No predisposing factor for the formation of the pneumothorax was identified as the radiography revealed only bronchitis and blood tests were normal, the patient was thus discharged after 24 h, with the recommendations for observing the breathing pattern. Initially, spontaneous pneumothorax was suspected. The antibiotics were administered since bacterial pneumonia, although not confirmed on chest x-ray, is the main cause of pneumothorax in dogs is lung parenchyma disease. With the worsening of the clinical condition of the patient, CT was performed and did not demonstrate any findings that would justify the presence of pneumothorax. Despite the placement of the chest tube for facilitating the management of thoracentesis, there was no stabilization of the condition, enhancing the frequency of centesis procedures, which led to the decision to euthanize. The microscopic examination of the pulmonary alterations was decisive for the diagnostic conclusion. The visualization of the accumulation of foamy intra-alveolar macrophages, occasionally multinucleate, associated with cholesterol crystals, was responsible for the diagnosis of EnLP. This condition is rarely described in dogs and as in the present report, it is a noninfectious inflammatory condition, characterized by intra- or extracellular globules of lipid in the alveolar spaces. In the present report, although it was not possible to determine the etiology of EnLP, we can conclude that although rare, it can affect dogs and can generate severe clinical repercussions.